Institutions-augmented solow model and income clubs - Tebaldi, Edinaldo; Mohan, Ramesh (A Economia em Revista - AERE, 2011)
Growth economists still face major challenges and limitations to incorporate institutions into the standard growth framework. This article develops a simple institutions-augmented Solow growth model –that can be used in the classroom and for policy discussions –that accounts for the interactions between institutions and factor-productivity and examine the impacts of the quality of institutions on levels and growth rates of output. The institutions-augmented growth model shows that differences in the quality of institutions preclude income convergence and determine both the level and the growth rate of output per worker. The model also shows that poor institutions induce poverty traps. Furthermore, the income gap between rich and poor countries will not disappear if poor countries’ institutions do not improve relative to their rich counterpart.